Editorial: The search for truth: common ground between science and religion - Aragón Vargas, Luis Fernando (2022)
This editorial is an improved version of a lecture with the same name that was presented in the context of the Chair of Religious Studies, School of Philosophy, Universidad de Costa Rica. The importance of truth is highlighted, and a message is presented on the common ground shared by science and religion, along the same lines of previous articles and editorials published in this review on the philosophy of science. Furthermore, the editorial insists on the moral responsibility of those of us that are devoted to science, research and academia in a university milieu—the responsibility to contribute to knowledge.